2009
DOI: 10.1017/s0266462309990663
|View full text |Cite
|
Sign up to set email alerts
|

The health technology assessment adaptation toolkit: Description and use

Abstract: Objectives: Adapting health technology assessment (HTA) reports for different contexts could reduce the need for multiple reports on the same health technology with resultant saving of time and resources. This article describes an instrument, the adaptation toolkit, which has been developed to aid in the process of adaptation of HTA reports. Methods: The toolkit was developed by a partnership of HTA agencies and networks from across Europe. The role of the toolkit is to guide the user through the process of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 6 publications
(13 reference statements)
1
23
0
Order By: Relevance
“…Thirty-nine percent of respondents indicated that there were no guidelines for conducting HTA in their countries, but 11% did not answer this question. Sixty-two percent said they used HTA reports that had been produced in other jurisdictions to help in their decisions, which agrees with findings from other authors (15)(16)(17)(18)(19)(20)(21). HTA work produced in different contexts is usually adapted to the local situation in order to be used in the decision-making process.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thirty-nine percent of respondents indicated that there were no guidelines for conducting HTA in their countries, but 11% did not answer this question. Sixty-two percent said they used HTA reports that had been produced in other jurisdictions to help in their decisions, which agrees with findings from other authors (15)(16)(17)(18)(19)(20)(21). HTA work produced in different contexts is usually adapted to the local situation in order to be used in the decision-making process.…”
Section: Discussionsupporting
confidence: 81%
“…HTA work produced in different contexts is usually adapted to the local situation in order to be used in the decision-making process. When properly done, this saves time and money, prevents inefficiencies and duplication, and enables the transfer of knowledge between different situations (15,(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…At least intuitively, the production of transferable HTA reports might lessen the need for multiple reports on the same health technologies. And further, transnational dissemination of individual evaluation results might appear to save time and resources [15]. Practically speaking, however, it seems that the production of transferable information regarding the impact of individual treatments, the possession of comparative information regarding the effectiveness of individual technologies, will be significantly less useful in driving an individual HTA processes, like the French approach, than is currently imagined in the academic literature.…”
Section: Discussionmentioning
confidence: 99%
“…European policy analysts likewise support the establishment of a European drug pricing and reimbursement agency similar to the European Medicines Agency (EMA) [13]. Furthermore, they have suggested that comparative efficacy data should have a formal role in European drug approvals; and that European authorities should collaborate with national HTA agencies towards the better congruence of licensing and reimbursement requirements [14,15]. Additionally, the European Parliament's directive on patient rights and cross-border healthcare also supported more formalised cooperation between national HTA agencies through the European Network for Health Technology Assessment (EUnetHTA) [16].…”
Section: The Contextual Mediation Of Common Functional Pressuresmentioning
confidence: 99%
“…At the European level, the proliferation of national HTA agencies 62 has produced interest in cooperation and the exchange of HTA knowledge for the 63 purpose of reducing expenditure and the duplication of work programs [16,17,18]. At 64 the industry level too, there is support from major pharmaceutical companies for a 65 harmonization of HTA methods for the purpose of producing nationally transferable 66 results [19,20]. Policy analysts have also suggested the establishment of a European 67 drug pricing and reimbursement agency similar to the European Medicines Agency 68 (EMA) [21].…”
mentioning
confidence: 99%